1998
DOI: 10.1021/jo980758p
|View full text |Cite
|
Sign up to set email alerts
|

An Antifungal Cyclodepsipeptide, Cyclolithistide A, from the Sponge Theonella swinhoei

Abstract: A novel antifungal cyclic depsipeptide, cyclolithistide A (1), was isolated from a marine sponge, Theonella swinhoei. The structure of cyclolithistide A, which contains the unique amino acids 4-amino-3, 5-dihydroxyhexanoic acid, formyl-leucine, and chloroisoleucine, was elucidated through a combination of spectroscopic techniques. Thirteen additional specimens of T. swinhoei and three of Theonella conica were examined in this study. Many contained the two cyclic peptides, motuporin (2) and theonellapeptolide 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 32 publications
(37 reference statements)
1
59
0
Order By: Relevance
“…no. 94590), though previously discussed, 14 was not evaluated by the methods used herein. There were 14 compounds profiled as shown in Table 1 21 and theopederin J 11 (see Figure S8).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…no. 94590), though previously discussed, 14 was not evaluated by the methods used herein. There were 14 compounds profiled as shown in Table 1 21 and theopederin J 11 (see Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…The first phenotype is defined by a characteristic red-purple ectosome and a cream-colored endosome, and more than 15 such samples have been examined by our group. 14 We found that the major constituents varied among the swinholides, motuporin or theonellapeptolide Id, but not all compounds were present in all collections. The second also possesses a redpurple ectosome but with a yellow to orange interior.…”
mentioning
confidence: 94%
See 3 more Smart Citations